A transfer function method for the continuous assessment of baroreflex control of renal sympathetic nerve activity in rats - Kanbar, Roy (2007)
The present study examined whether the gain of the transfer function relating cardiac-related rhythm of renal sympathetic nerve activity (RSNA) to arterial pressure (AP) pulse might serve as a spontaneous index of sympathetic baroreflex sensitivity (BRS). AP and RSNA were simultaneously recorded in conscious rats, either baroreceptor-intact (control, n = 11) or with partial denervation of baroreflex afferents [aortic baroreceptor denervated (ABD; n = 10)] during 1-h periods of spontaneous activity. Transfer gain was calculated over 58 adjacent 61.4-s periods (segmented into 10.2-s periods). Coherence between AP and RSNA was statistically (P < 0.05) significant in 90 ± 3% and 56 ± 10% of cases in control and ABD rats, respectively. Transfer gain was higher (P = 0.0049) in control [2.39 ± 0.13 normalized units (NU)/mmHg] than in ABD (1.48 ± 0.22 NU/mmHg) rats. In the pooled study sample, transfer gain correlated with sympathetic BRS estimated by the vasoactive drug injection technique (R = 0.75; P < 0.0001) and was inversely related to both time- (standard deviation; R = −0.74; P = 0.0001) and frequency-domain [total spectral power (0.00028–2.5 Hz); R = −0.82; P < 0.0001] indices of AP variability. In control rats, transfer gain exhibited large fluctuations (coefficient of variation: 34 ± 3%) that were not consistently related to changes in the mean level of AP, heart rate, or RSNA. In conclusion, the transfer function method provides a continuous, functionally relevant index of sympathetic BRS and reveals that the latter fluctuates widely over time.